Kinematic and kinetic comparisons between spot, crossover and upward jump throwings in handball - Moghaddam, M. S.; Mohammadi, M. R. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
Throwing is one of the most important skills in handball in which two basic factors are of importance with regard to the efficiency of shots i.e. accuracy and velocity. A 2-Dimensional analysis of different throws i.e. on the spot, with a cross-over step, and with upward jump has been undertaken. Eighteen high-performance handball players took part in this study. The average values of basic parameters of physical characteristics of subjects were: 80.2 ±6.1 Kg (body mass), 184.8 ± 4 cm (body height), and 19.79 ± 0.63 years of age. The main aim of present study was to establish a valuable kinematic and kinetic comparison between different types of throws in handball. Statistically significant differences were found between maximal ball velocity during throws with cross-over step and ball velocity during other analyzed throws. In addition to the high velocity in this throw, the energy and power consumptions were also higher in magnitude comparing with other throws. The results obtained by this study agreed well with the results reported by other researchers.